Serum Phosphate and 1-Year Outcome in Patients With Acute Ischemic Stroke and Transient Ischemic Attack - Zhang, Jun-Fang; Jing, Jing; Meng, Xia; Pan, Yuesong; Wang, Yi-Long; Zhao, Xing-Quan; Lin, Jin-Xi; Han, Xin-Sheng; Song, Bin-Bin; Jia, Zheng-Chang; Wu, Song-Di; Chen, Xiao-Fei; et al. (Frontiers in Neurology, 2021)
Objective: To determine the association between serum phosphate level and 1-year clinical outcomes in patients with acute ischemic stroke and transient ischemic attack. Methods: We included 7353 patients with acute ischemic stroke and transient ischemic attack from the China National Stroke Registry III for analysis. Participants were divided into 4 groups according to serum phosphate quartiles. Composite end point included recurrent stroke, myocardial infarction, other ischemic vascular events, and all-cause mortality. Poor functional outcome is defined as modified Rankin Scale score of 3 to 6. Multivariable Cox regression or logistic regression was used to evaluate the independent association of serum phosphate with 1-year all-cause mortality, recurrent stroke, composite end point and poor functional outcome. Results: The mean age of the included 7353 patients was 62.5 years, and 68.6% of them were men. Plotting hazard ratios over phosphate levels suggested a U-shaped association especially for recurrent stroke and composite end point, and therefore the third quartile group was set as reference group. Compared with the third quartile of phosphate (1.06-1.20 mmol/L), the adjusted hazard ratios/odds ratios (95% CI) of the lowest quartile (<0.94 mmol/L) were 0.98 (0.67-1.42) for all-cause mortality, 1.31 (1.05-1.64) for stroke recurrence, 1.26 (1.02-1.57) for composite end point, and 1.27 (1.01-1.61) for poor functional outcome, and the adjusted odds ratio of the highest quartile (≥1.2 mmol/L) was 1.40 (1.11-1.77) for poor functional outcome. Conclusions: Serum phosphate may be an independent predictor of stroke recurrence, composite end point and poor functional outcome after ischemic stroke.